Evaluate The Ease of Removing New Root Canal Medicament from The Artificial Secondary Canals in The Middle Third of Root Canal - عزيز عبد الله (Latakia University Journal -Medical Sciences Series, 2024)
Objective: The aim of this research was to study the ease of removing the Hanse Dent Endomix medicament from the artificial secondary canals in the middle third in comparison with the ledermix and calcium hydroxide. Materials and Methods: This study was conducted on a sample of 30 single-canal extracted human teeth, whose crowns were cut and standardized to length (15 mm), then prepared to a size of 35# 0.06. secondary canals were made in the apical third using a 40# file mounted on a micromotor handpiece. the teeth Then were filled with three medicaments and were divided accordingly as follows: the first group (10 teeth): calcium hydroxide medicament, the second (10 teeth): Hanse Dent Endomix medicament, and the third (10 teeth) Ledermix. the ease of removing the medicaments from the secondary canals was evaluated, and statistical tests were performed. Results: There was a statistically significant difference in the ease of removing the three dressings, as the ease was graded from higher to lower as follows: Hanse Dent Endomix, followed by Lidermix, and finally calcium hydroxide. Conclusion: Within the limitations of this study, it can be concluded that the Hanse Dent Endomix medicament is easily removed from secondary canals in the middle third, and thus it can be applied in root canal systems with complex anatomy.